1995
DOI: 10.1007/bf02887946
|View full text |Cite
|
Sign up to set email alerts
|

Effect of captopril on membrane currents of ventricular myocytes

Abstract: Using whole-cell patch-clamp technique, the present study examined the effects of captopril on membrane currents of ventricular myocytes. The results were as follow: when the concentration of captopril was 6 x 10(-4)mol, the fast inward sodium current and slow inward calcium current were all decreased significantly (P < 0.05). Besides, when the concentration exceeds 10(-3)mol, the delayed rectifier potassium current was increased (P < 0.05) as well. But if the experimental concentration was under 6 x 10(-4)mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The drug stimulates prostaglandin production and release IL-2 production [4], and possesses immunosuppressant activity. Besides its vasodilative effects, it possesses inhibiting effects on hypertrophy and remodeling of myocardium without interference with the metabolism of fatty acid, and can improve the patients' quality of life [5,6]. Some experimental studies have suggested that captopril has antiarrhythmic activity, a reduction of arrhythmias induced by isehemia, reperfusion, or digitalis toxicity [7].…”
Section: Introductionmentioning
confidence: 99%
“…The drug stimulates prostaglandin production and release IL-2 production [4], and possesses immunosuppressant activity. Besides its vasodilative effects, it possesses inhibiting effects on hypertrophy and remodeling of myocardium without interference with the metabolism of fatty acid, and can improve the patients' quality of life [5,6]. Some experimental studies have suggested that captopril has antiarrhythmic activity, a reduction of arrhythmias induced by isehemia, reperfusion, or digitalis toxicity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Tourmaline is a kind of borosilicate complex mineral, whose general chemical formula can be written as XY 3 Z 6 [Si 6 O 18 ] [BO 3 ] 3 W 4 , where X is Na + , Ca 2+ , K + , or vacancy; Y is Mg 2+ , Fe 2+ , Mn 2+ , Al 3+ , Mn 3+ , Cr 3+ , Ti 4+ , or Li + ; Z is Al 3+ , V 3+ ,Cr 3+ , or Mg 2+ , and W is OH -, F -, or O 2- [4][5], has the property of spontaneous polarity and far infrared emission. It is found that the high far infrared emission of tourmaline is due to cell volume [6], pyroelectric effect [7] chemical component [8] and the infrared activity of vibration in its crystal structure [9], Yang et al [10] has found the far infrared emissivity of black tourmaline which is calcinated in reduction atmosphere is higher than Far-infrared ceramic powder. Meng [11] has indicated that tourmaline powders exhibit improved far infrared emission properties as the particle size decreases, and the emissivity values of the samples with D50 size of 2.67 μm and 0.2 μm are 0.973 and 0.991, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recently with the increasing of transportation and vehicle's weight, more and more concrete beams are not satisfied with bearing capacity and reinforcement which is normally required. Currently concrete beams are mainly strengthened by carbon fiber sheet or strengthened jointly by carbon fiber sheet and external prestressing to reinforce in the engineering community [1][2][3][4][5]. Base on two groups of comparison tests of bearing capacity of six rectangle section of steel concrete beams with different strength grades, the research analyzed the effect of concrete beams strengthened by carbon fiber sheet and strengthened jointly by carbon fiber sheet and external prestressing on the bearing capacity, failure modes, strain states, rigidity and ductility.…”
Section: Introductionmentioning
confidence: 99%